The heptad repeat domain 1 of Mitofusin has membrane destabilization function in mitochondrial fusion. (16th April 2018) - Daste, Frédéric; Sauvanet, Cécile; Bavdek, Andrej; Baye, James; Pierre, Fabienne; Le Borgne, Rémi; David, Claudine; Rojo, Manuel; Fuchs, Patrick; Tareste, David
Abstract: Mitochondria are double‐membrane‐bound organelles that constantly change shape through membrane fusion and fission. Outer mitochondrial membrane fusion is controlled by Mitofusin, whose molecular architecture consists of an N‐terminal GTPase domain, a first heptad repeat domain (HR1), two transmembrane domains, and a second heptad repeat domain (HR2). The mode of action of Mitofusin and the specific roles played by each of these functional domains in mitochondrial fusion are not fully understood. Here, using a combination of in situ and in vitro fusion assays, we show that HR1 induces membrane fusion and possesses a conserved amphipathic helix that folds upon interaction with the lipid bilayer surface. Our results strongly suggest that HR1 facilitates membrane fusion by destabilizing the lipid bilayer structure, notably in membrane regions presenting lipid packing defects. This mechanism for fusion is thus distinct from that described for the heptad repeat domains of SNARE and viral proteins, which assemble as membrane‐bridging complexes, triggering close membrane apposition and fusion, and is more closely related to that of the C‐terminal amphipathic tail of the Atlastin protein. Synopsis: The GTPase Mitofusin mediates mitochondrial fusion, but the underlying mechanism of membrane fusion remains unclear. This study shows that the amphipathic nature of the heptad repeat domain 1 (HR1) of Mitofusin perturbs the lipid bilayer structure to drive mitochondrial fusion. HR1 is required for Mitofusin‐mediated mitochondrial fusion in cultured cells, and induces liposome fusion in vitro . The membrane fusion activity of HR1 is associated with its capacity to insert into lipid bilayers, notably in regions presenting lipid packing defects. This property is conferred by a conserved amphipathic helix located at the C‐terminus of the HR1 sequence. Abstract : The GTPase Mitofusin mediates mitochondrial fusion, but the underlying mechanism of membrane fusion remains unclear. This study shows that the amphipathic nature of the heptad repeat domain 1 (HR1) of Mitofusin perturbs the lipid bilayer structure to drive mitochondrial fusion.